A Study on the Role of Micro Economic Policy: Exploring the Relationship between Micro Economic Policy and Macro Economics (Journal of Advances and Scholarly Researches in Allied Education, 2013)
Macro Economicsis a branch of economics dealing with the performance, structure, behavior, anddecision-making of the entire economy. This includes a national, regional, or globaleconomy with microeconomics, macroeconomics is one of the two mostgeneral fields in economics.